2013
DOI: 10.1002/jmri.24430
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between two types of improved motion‐sensitized driven‐equilibrium (iMSDE) for intracranial black‐blood imaging at 3.0 tesla

Abstract: Our results show that iMSDE-2 demonstrated smaller loss in signal and less spatial variation compared with iMSDE-1, we conjecture due to the improved eddy current compensation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 16 publications
0
31
0
Order By: Relevance
“…Nagao et al [13] used a 3D TSE sequence implemented with a blackblood technique called motion-sensitized driven equilibrium (MSDE) preparation (TSE-MSDE). With MSDE preparation, signals from flowing blood are selectively suppressed through phase-dispersion induced by flow-sensitizing gradients [16][17][18][19][20]. Nagao et al [13] reported that TSE-MSDE could increase the sensitivity in detecting metastases and shorten the reading time compared to a conventional 3D GRE sequence.…”
Section: Introductionmentioning
confidence: 97%
“…Nagao et al [13] used a 3D TSE sequence implemented with a blackblood technique called motion-sensitized driven equilibrium (MSDE) preparation (TSE-MSDE). With MSDE preparation, signals from flowing blood are selectively suppressed through phase-dispersion induced by flow-sensitizing gradients [16][17][18][19][20]. Nagao et al [13] reported that TSE-MSDE could increase the sensitivity in detecting metastases and shorten the reading time compared to a conventional 3D GRE sequence.…”
Section: Introductionmentioning
confidence: 97%
“…Next, we will discuss the imaging principles of Dynamic iMSDE SSFP. The iMSDE 4,5) is a technique that induces spin dephasing using a magnetic field gradient that is sensitive to motion called the motion-sensitized gradient (MSG). The feature of this technology is that there are no limitations in imaging sections or range, and it can be combined with various other imaging methods.…”
Section: Discussionmentioning
confidence: 99%
“…The number of 180° refocusing pulses in the control module is two for AccASL, and four for eAccASL (Figure B,C). An additional block of unipolar gradients similar to the ones used in the labeling scheme was inserted before the first 90° excitation pulse to optimize eddy current cancelation . Duration of T2‐preparation for both AccASL and eAccASL was 20 ms.…”
Section: Methodsmentioning
confidence: 99%
“…An additional block of unipolar gradients similar to the ones used in the labeling scheme was inserted before the first 90° excitation pulse to optimize eddy current cancelation. 9 Duration of T2-preparation for both AccASL and eAccASL was 20 ms. The MSG strength is defined by the acceleration causing a phase change of π (AENC: acceleration-encoding).…”
Section: Eaccasl Schemementioning
confidence: 99%